0813 Post-Pinealectomy Insomnia and Melatonin Therapy. (25th May 2022) - Johal, Arminder; Manchanda, Shalini; Bodkin, Cynthia; Stahl, Stephanie
Abstract: Introduction: Melatonin is a hormone produced in the pineal gland that has an important role in sleep; immune, neurologic, psychiatric, metabolic, and endocrinologic function; cardiac-autonomic regulation and even cancer risk. We present a case of insomnia, somnambulism, dream enactment, and periodic limb movements of sleep (PLMS) after a pinealectomy. Report of Cases: A 40-year-old woman with a history of a complete pinealectomy due to a pineal cyst presented to the sleep medicine clinic. Shortly after the pinealectomy, she developed sleep onset and maintenance insomnia. Two years later she developed somnambulism, and four years later she developed dream enactment and PLMS. She reported no prior treatments for her sleep issues, including no history of melatonin use. On average, her total sleep time (TST) was 2-8 hours/night with awakenings every 2 hours. Sleep latency was 10-45 minutes. Polysomnograghy demonstrated an apnea-hypopnea index of 0.6/hr, PLM index of 68.1/hr, normal REM atonia, and no complex behaviors. The patient started 1mg immediate release (IR) melatonin, which did not help her insomnia, but parasomnias resolved. She had improvement in her PLMS with iron supplementation and melatonin. The melatonin dose was increased to 3mg IR which helped increase her TST to 4-8 hours. She was switched to 3mg extended release (ER) melatonin, and then increased to 4mg ER. She obtained the most benefit for her insomnia with 1mg IR plus 4mg ER with sleep latency reduced to 5-10 minutes and TST improved up to 7.5 hours with rare awakenings. Conclusion: Pinealectomy in humans is rarely reported. Most data about the consequences of pinealectomy and pathophysiology of melatonin come from animal research. Melatonin level after pinealectomy is often undetectable or severely diminished. Current limited literature on patients with pinealectomy consists of case reports about patients who experienced insomnia, non-24-hour sleep-wake rhythm disorder [SSM1] and mood disorders. Melatonin doses ranging from 0.5mg to 14mg IR and up to 5mg ER have been trialed with most patients having symptomatic improvement with doses above 3mg. We found that a combination of 1mg immediate and 4mg extended release melatonin was the most beneficial for our patient. Support (If Any):